(untitled) (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This study aims to deconstruct the meaning of “fitrah” (الفطرة), a central concept in Islamic theology traditionally understood as the ’natural disposition’ or ’primordial tendency’ of humans towards monotheism. Based on the key verse Q.S. Ar-Rum (30:30), the concept (الفطرة) is conventionally interpreted in Islamic theological discourse as the pure and monotheistic primordial disposition of humans. This understanding assumes ’fitrah’ as an ahistorical essence that exists fully within humans. This study aims to deconstruct this metaphysical conception through Jacques Derrida’s framework of deconstructive hermeneutics, focusing on the philosopher’s critique of the ’metaphysics of presence.’ The analysis is conducted on the corpus of classical exegesis (al-Ṭabarī, al-Rāzī, and Ibn Kathīr) to uncover how the meaning of ’fitrah’ is constructed textually. The focus of the analysis is traced on the operation of the mechanisms of différance and fundamental binary opposition (for example, fiṭrah (divine originality) vs. taghyīr (change/contamination), ḥanīf (Islam) vs. yahūdī/naṣrānī (deviation), as well as primordial disposition vs. parental influence) which hegemically structure the meaning of “fitrah.” This study argues that “fitrah” in classical exegesis is not a stable and autonomous presence, but rather a logocentric construct whose meaning is always supported and haunted by the trace of the "other" (l’autre), in this case, the cultural particularities and non-Islamic religious affiliations that are attempted to be excluded. The meaning of “fitrah” therefore is never fully present, but is always deferred and relational. The implications of these findings are twofold. Theologically, this deconstruction subverts the ideas of theological determinism and rigid originality of revelation by showing that the meaning of ’fitrah’ is never final. From an anthropological-philosophical perspective, this analysis dismantles essentialism in the definition of ’humanity’ tied to specific religious identities, thereby demanding a rearticulation of human identity that is more fluid, ethical, and open to otherness.